INDIKATOR KUALITAS PELAYANAN HOME CARE PADA PASIEN STROKE: SEBUAH REVIEW: Indikator kualitas pelayanan home care - Nur Chayati; Christantie Effendy; Setyopranoto Setyopranoto (Jurnal Kesehatan Komunitas, 2019)
Background: One method to identify the level of performance is using quality of care indicators. Even though many quality indicators of health care have been announced, those which specify in home care services are limited in that none of them describe the stroke patients’ condition. The purposes of this study are to determine through systematic literature review what methods can be used to assess the quality of home care that patients received and to identify what components can be used as a determinant of the quality of home care services. Method: Google Scholar, EBSCO, ProQuest and PubMed database websites were searched for articles and information. Results: The method that was used is a qualitative study using a literature review with quantitative analysis of a previously accepted research instrument with a questionnaire that has been widely available and considered reliable. The researchers identified thematic differentiation in grouping the quality indicators used by those articles, however most of them are classified as outcome indicators, one as process indicator, and none as structure or input indicator. Overall quality indicators in home care that are used by the three articles are based on the Home Care Quality Indicators Instrument (HCQIs). Conclusions: Several studies discussed home care quality indicators but no articles specifically analyze home care provision for stroke patients. Further research is needed to clarify the components indicators for stroke patients and more importantly, these indicators should be valid, and reliable.